The dinoflagellate genera Gambierdiscus and Ostreopsis from subtropical Raoul Island and North Meyer Island, Kermadec Islands - Lesley L. Rhodes; Kirsty F. Smith; Arjun Verma; Sam Murray; D. Tim Harwood; Tom Trnski (New Zealand Journal of Marine and Freshwater Research, 2017)
An expedition to North Meyer Island, Kermadec Islands, in November 2015, resulted in the isolation of two Gambierdiscus species, G. australes and a previously unknown Gambierdiscus species maintained in the Cawthron Institute Culture Collection of Micro‐algae as CAWD242. Identifications were based on morphology and DNA sequence data analysis. Nine isolates of G. australes produced maitotoxin‐1 (MTX‐1) ranging from present (detectable but below the confidence level) to 36.6 pg per cell. One further isolate did not produce MTX‐1, but all G. australes isolates produced putative MTX‐3. Isolate CAWD242 was negative for MTX‐1 but produced MTX‐3. Ostreopsis sp. 3 isolated from samples collected during an earlier expedition in 2013 produced low concentrations of palytoxin (PLTX)‐like compounds (0.013 pg per cell), but an isolate of the same species from samples collected in 2015 was non‐toxic. Other dinoflagellates isolated and identified were Coolia malayensis , Amphidinium carterae and Prorocentrum hoffmannianum .